WORKSHOP PENERAPAN TEKNOLOGI WEB SERVICE PADA APLIKASI IKUTPEDULI UNTUK PENGGALANGAN BANTUAN DAN PROMOSI KEGIATAN SOSIAL DI TASIKMALAYA - Irfan Darmawan; R. Wahjoe Witjaksono; Alam Rahmatulloh; Rohmat Gunawan; Randi Rizal (El-Khidmat, 2024)
Sedekah Nasi community is a social organization in society that regularly spreads goodness by distributing rice to those in need. Some of the obstacles faced by the  Sedekah Nasi community include: limited facilities for disseminating information on aid-raising services and limited information for people who will become donors. So that the operational activities of the  Sedekah Nasi community are more optimal, in this service activity it is proposed to apply web service technology which is packaged in the form of an application with the name ikutpeduli. The participatecare application is designed to provide donation services in the form of goods or money electronically through registered bank channels. The stages of service activities carried out include: socialization of web service technology on the participate care application, application testing, evaluation of service activities. The service activity was held on Saturday 25 May 2024 at 13:30 at SD Baiturrahman Kec. Cipedes, Tasikmalaya City, West Java. Followed by 19 people consisting of: the administrators of the Sedekah Nasi community, the administrators of the Nasi Jumat community and the community service implementation team from Telkom University and Siliwangi University.